Improving weaning practices in the Caribbean : 6 self learning modules for community workers - Isaacs, Patricia (CFNI KingstonJM, 1986)
Outlines six modules containing information, questions, and activities that can help the community worker to teach others about the weaning process and healthy weaning habits. Modules discuss the characteristics of good food; nutritional food for the family; preparing and serving safe weaning foods; identifying and resolving nutritional problems in young children; teaching methodologies; and techniques for effective work with families.